Treatment Access and Caregiver Experience in Pediatric Rhabdomyosarcoma: Results of an Online Survey - Jamil Almohtasib; Timothy C. Boswell; Candace F. Granberg; Patricio C. Gargollo (Children)
Background/Objectives: Pediatric rhabdomyosarcoma is a rare and poorly understood disease. Patients and parents can have varying experiences including barriers to care, time to treatment, and treatments offered. Here, we report on patient experiences regarding their care of pediatric rhabdomyosarcoma. Methods: Two separate online parent support groups were invited to participate in a survey. The survey included questions that sought to collect patient demographics, history of rhabdomyosarcoma, treatment timelines, and barriers to care. Results: A total of 215 surveys were completed. The average time from diagnosis to treatment was 12 days (SD = 14). Only 26% were offered fertility preservation prior to treatment. For patients with recurrence, an average of 75 days passed between detection of recurrence and treatment re-initiation. Patients traveled to centers with a dedicated sarcoma program in 52% of the cases. A total of 42% of parents sought a second opinion. Of those, the majority had to wait between one week and one month to be seen by another expert. Conclusions: The data collected from the survey suggests there are several opportunities to improve care among patients with pediatric rhabdomyosarcoma. Many patients may benefit from more efficient rhabdomyosarcoma referral networks, delivering patients to experts who can quickly begin multidisciplinary treatment.